Implementation of Iso 14001-Based Environmental Management System in Cleanliness and Garden Maintenance at the Jakarta Presidential Palace - Yeni Astuti; Achmad Husen; Dian Alfia Purwandari; Akhmad Qosasih; Danang Pratomo (Publikasi Indonesia, 2025)
The ISO 14001-based Environmental Management System (EMS) provides a structured framework to improve an organization's environmental performance. As the central seat of government, the Jakarta Presidential Palace plays a strategic role in demonstrating a strong commitment to sustainable environmental management. This article aims to analyze the implementation of ISO 14001 in managing cleanliness and maintaining gardens within the Palace grounds. The study is based on literature reviews and analysis of ISO standard documentation and environmental management practices. The results show that the ISO 14001 approach helps improve management efficiency, prevent pollution, and support the conservation of garden vegetation. However, challenges remain, especially in raising internal awareness, maintaining proper documentation, and conducting sustainability audits. This study recommends integrating ISO 14001 with the institution's work culture as a strategic step toward more effective green management.